Theoretical Design of a Belt Sander Wood Sanding Machine for Small-Scale Industries - Candra Prayoga Aditama Paputungan; Herotje Siwi (Global Writing Academica Researching and Publishing, 2026)
Manual wood sanding in small workshops requires considerable time and labor but may produce inconsistent surface quality. This study aimed to develop a theoretical design for a belt-sander wood sanding machine and determine the specifications of its main components. An engineering design approach was used, comprising a literature review, identification of design requirements, component selection, preparation of two- and three-dimensional AutoCAD drawings, and analytical calculations for the motor, pulley and V-belt transmission, rollers, shaft, and frame. The proposed machine uses a 1 HP (0.746 kW), 1390 rpm electric motor, 80 mm driving and 120 mm driven pulleys, an A-type V-belt, 100 mm rollers, a 25 mm S45C shaft, UCP205 bearings, and a 40 × 40 × 2 mm hollow-steel frame. The calculations yielded a drive-roller speed of 926.67 rpm, motor torque of 5.13 N·m, theoretical roller torque of 7.70 N·m, sanding-belt speed of 4.85 m/s, tangential force of 154 N, theoretical V-belt length of 1115 mm, roller mass of approximately 5.55 kg, and shaft torsional shear stress of 2.51 N/mm². These results provide a technical basis for prototype development; however, operational feasibility remains unconfirmed because combined loading, vibration, surface roughness, productivity, and actual power consumption have not been experimentally evaluated.